Jin Opera Huhu: A Critical Sound Analysis of Cultural Representation in Conventional Jin Opera - Guanzhou Li; Ahmad Faudz bin Musib; Noris Mohd Norowi; Pan Jian (BioResources, 2025)
A comprehensive acoustic analysis was carried out for the huhu, a betelwood instrument from the Jin opera. Techniques included an acoustic visualiser and Fast Fourier Transform (FFT). The harmonic structure, frequency distribution, and timbre quality of the instrument were investigated, focusing on the effect of the use of leather finger cuff on the sound produced. Spectral analyses revealed complex overtones and distinctive spectral patterns for different playing techniques, ranging from 324.47 to 10,277.08 Hz. Finger cuffs significantly altered the harmonic content and timbre. The study utilised high fidelity equipment to conduct multiple recordings under controlled conditions to capture subtle acoustic changes. Statistical analysis of the frequency data revealed a consistent overtone structure, while an acoustic visualiser examined the relationship between playing technique and sound intensity. The analyses emphasised how traditional playing methods (particularly fretting) affect acoustic output. By documenting the current acoustic characteristics of the huhu, this work provides insight into its musical and cultural significance, contributes to the preservation of traditional musical heritage and provides a scientific basis for understanding the unique acoustic characteristics of betel nut wood.